2009
DOI: 10.1158/1078-0432.ccr-08-2190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recently Identified Prostate Cancer Susceptibility Loci in a Population-based Study: Associations with Family History and Clinical Features

Abstract: Purpose: Two recent genome-wide association studies have highlighted several single nucleotide polymorphisms (SNPs) purported to be associated with prostate cancer risk.We investigated the significance of these SNPs in a population-based study of Caucasian men, testing the effects of each SNP in relation to family history of prostate cancer and the clinicopathologic features of the disease. Experimental Design: We genotyped 13 SNPs in 1,308 prostate cancer patients and 1,267 unaffected controls frequency match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
46
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
(39 reference statements)
3
46
1
2
Order By: Relevance
“…Although the associations for some SNPs, such as those at 8q24, were stronger among patients with aggressive PCa in some studies when each type of case is compared versus unaffected controls (35,36), these SNPs were not associated with PCa aggressiveness in any of the studies when patients with more or less aggressive PCa were directly compared. Indeed, three large studies that were published recently each concluded the null association of the PCa risk-associated SNPs with PCa aggressiveness (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the associations for some SNPs, such as those at 8q24, were stronger among patients with aggressive PCa in some studies when each type of case is compared versus unaffected controls (35,36), these SNPs were not associated with PCa aggressiveness in any of the studies when patients with more or less aggressive PCa were directly compared. Indeed, three large studies that were published recently each concluded the null association of the PCa risk-associated SNPs with PCa aggressiveness (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, none of these PCa risk-associated SNPs consistently distinguish risk for more or less aggressive cancer (26)(27)(28), nor are they associated with prostate cancer-specific mortality (29). As a result, there has been much debate regarding the clinical utility of these SNPs as a risk stratification tool (30,31).…”
mentioning
confidence: 99%
“…However, few studies have been able to show a clear and replicated association between these genetic variants and prostate cancer aggressiveness (20). To our knowledge, only 8q24 SNPs (rs1447295 and rs6983267) have been exposed as markers of aggressiveness, mainly through Gleason score, in multiple studies (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Среди причин, которые могли быть причастны к раз-витию РПЖ, отмечали: географическое место прожива-ния [19], возраст [19], инфекционные воспалительные процессы [2], этнических фон [22], диету [29], половые гормоны [15], семейные [1,3,7,13,23,30] и наследствен-ные факторы [1,9,11,20,24]. Положительный семейный анамнез является одним из самых сильных эпидемиоло-гических факторов риска развития РПЖ [11,20,24], кото-рый увеличивает риск для родственников первой степени более чем два раза.…”
unclassified
“…Положительный семейный анамнез является одним из самых сильных эпидемиоло-гических факторов риска развития РПЖ [11,20,24], кото-рый увеличивает риск для родственников первой степени более чем два раза. Вместе с тем, семейные и наслед-ственные факторы, вызывающие развитие РПЖ, не впол-не понятны.…”
unclassified